1999
DOI: 10.1074/jbc.274.27.19072
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Topology of Proton-pumping Escherichia coli Transhydrogenase Determined by Cysteine Labeling

Abstract: The membrane topology of proton-pumping nicotinamide-nucleotide transhydrogenase from Escherichia coli was determined by site-specific chemical labeling. A His-tagged cysteine-free transhydrogenase was used to introduce unique cysteines in positions corresponding to potential membrane loops. The cysteines were reacted with fluorescent reagents, fluorescein 5-maleimide or 2-[(4 -maleimidyl)anilino]naphthalene-6-sulfonic acid, in both intact cells and inside-out vesicles. Labeled transhydrogenase was purified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 38 publications
1
56
0
Order By: Relevance
“…In previous studies, fluorescein maleimide, which at neutral pH is a dianion and membrane-impermeable, proved to be a useful fluorophore to determine the membrane topology of integral membrane proteins by modification of engineered cysteines (21)(22)(23). It was found that this thiol reagent does not react with cysteines in the lipidic membrane environment, but readily reacts with cysteines in polar loop regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, fluorescein maleimide, which at neutral pH is a dianion and membrane-impermeable, proved to be a useful fluorophore to determine the membrane topology of integral membrane proteins by modification of engineered cysteines (21)(22)(23). It was found that this thiol reagent does not react with cysteines in the lipidic membrane environment, but readily reacts with cysteines in polar loop regions.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [21][22][23]. Fluorescein maleimide is therefore a suitable probe to determine whether the cysteine is situated in a polar loop region or within a lipidic membrane region.…”
Section: Construction Expression and Activity Of Single Cysteine Mumentioning
confidence: 99%
“…[38]. Thus, the single-subunit enzyme from animal mitochondria was thought to have 14 transmembrane helices (TM) per protomer, the Modified from Ref.…”
Section: The DI Dii and Diii Components Of Transhydrogenasementioning
confidence: 99%
“…1). Cysteine mutants were introduced in E. coli TH between all predicted transmembrane ␣-helices, and fluorescence labeling experiments defined their orientation with respect to the membrane (25)(26)(27). One transmembrane helix, H5, predicted for bovine TH does not occur in the E. coli enzyme, corresponding to the division between ␣ and ␤ subunits.…”
Section: Nicotinamide Nucleotide Transhydrogenases (Th)mentioning
confidence: 99%